2015
DOI: 10.1007/s10157-015-1131-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tonsillectomy combined with steroid pulse therapy on immunoglobulin A nephropathy depending on histological classification: a multicenter study

Abstract: TSP may have a beneficial effect on the clinical course in IgAN patients with mild to moderate glomerular and interstitial lesions, particularly with distinct mesangial cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The Kidney Disease Improving Global Outcomes (KDIGO) Glomerulonephritis Work Group clinical practice guidelines for GN recommend that patients with persistent proteinuria ≥1 g/day, despite 3–6 months of optimized supportive care (including ACE-I or ARB's and blood pressure control) and a glomerular filtration rate (GFR) <50 ml/min per 1.73 m 2 receive a 6-month course of steroid therapy [6]. As an alternative treatment, tonsillectomy combined with steroid pulse (TSP) administration may be useful for inducing complete remission in patients with IgAN who have persistent proteinuria, although its long-term effectiveness remains uncertain [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…The Kidney Disease Improving Global Outcomes (KDIGO) Glomerulonephritis Work Group clinical practice guidelines for GN recommend that patients with persistent proteinuria ≥1 g/day, despite 3–6 months of optimized supportive care (including ACE-I or ARB's and blood pressure control) and a glomerular filtration rate (GFR) <50 ml/min per 1.73 m 2 receive a 6-month course of steroid therapy [6]. As an alternative treatment, tonsillectomy combined with steroid pulse (TSP) administration may be useful for inducing complete remission in patients with IgAN who have persistent proteinuria, although its long-term effectiveness remains uncertain [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Miyamoto et al reported that TSP had an impact on achieving clinical remission in only the group with histological grade 3 of the 2nd version clinical guideline for IgAN in Japan and M1 in their multicenter retrospective cohort study in 284 patients with IgAN who received TSP or corticosteroid therapy or conservative therapy [ 24 ]. In their study, the effect of TSP was compared to that of conservative therapy and they also found a significant superior effect of corticosteroid therapy including steroid pulses compared to that of conservative therapy in the group with histological grade 3.…”
Section: Discussionmentioning
confidence: 99%